Submucosal uterine fibroid prolapsed into vagina in a symptomatic patient with IUS. (16th April 2014) - Matytsina-Quinlan, Lyubov; Matytsina, Laura
Abstract : A female patient in her mid 40s presents with heavy menstrual bleeding (HMB) and a history of spotting/irregular light per vagina (PV) bleeding since intrauterine system (IUS) insertion 1 year ago. She is known to have submucosal uterine fibroid (SMUF). The patient reported abdominal pain and sudden onset of 'miscarriage-like' HMB with clots 2 days ago. On speculum examination there was a smooth round-shaped mass lying over the external cervical os. On bimanual examination PV, a round-shaped smooth mass of a walnut's size was palpable in the upper third of the vagina. Subsequent ultrasound imaging revealed an SMUF prolapsed into the vagina. Further surgical treatment was undertaken. Histology showed a fibroid (leiomyoma) with no evidence of malignancy.